2004
DOI: 10.1111/j.1440-1665.2004.02131.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry and Islam

Abstract: Islam is based on unity and core values of compassion, justice and benevolence. Islamic psychiatry has a proud early history, and advances are occurring. There is an opportunity for the profession of psychiatry to bridge religious, ethnic and cultural boundaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In Arabic societies as in most societies, including Western, individuals with mental illness and their families are often stigmatized, rejected and isolated. This is because mental illness is still asso-ciated with evil spirits, effects of the evil eye, magic, and punishment from God, or with violence, addiction and suicide [44]. Due to guilt and shame, family members often refuse to discuss mental problems with non-family members, including medical physicians and mental health professionals [45].…”
Section: Expansion Of Mental Health Servicesmentioning
confidence: 99%
“…In Arabic societies as in most societies, including Western, individuals with mental illness and their families are often stigmatized, rejected and isolated. This is because mental illness is still asso-ciated with evil spirits, effects of the evil eye, magic, and punishment from God, or with violence, addiction and suicide [44]. Due to guilt and shame, family members often refuse to discuss mental problems with non-family members, including medical physicians and mental health professionals [45].…”
Section: Expansion Of Mental Health Servicesmentioning
confidence: 99%
“…Substance abuse is not considered an NSSI behavior in Western literature, but in this study it emerged as the second most common NSSI behavior by Jordanian students. This may be related to the fact that substance abuse in Islam is considered self-harmful and forbidden and is severely punished (Pridmore and Pasha, 2004). Other behaviors not commonly reported included eating fatty foods and masturbation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike US students (3.2%) and Greeks/Cypriots (12.3%), the majority of students in Jordan (72.6%) felt persons who self-harm are not religious. Although views in the Middle East vary, it is commonly believed that behaviors that harm the body are a manifestation of mental health issues, are a punishment by Allah, or are related to evil demonic possession (Pridmore and Pasha, 2004). In Jordan, students (50%) reported that it is easier for males to seek treatment for NSSI than females, while this was not the case in Greece/Cyprus (10%) and the United States (1.3%).…”
Section: Discussionmentioning
confidence: 99%
“…All the medical personnel is of Chechen origin [16]. Considering the fact that ethnic Chechens profess their religion to be Islam, it is important to note that mental disabilities may be seen through the prism of Islamic psychiatry, which views mental problems as a reflection of issues on a metaphysical level [21].…”
Section: Human Resourcesmentioning
confidence: 99%